The impact of a changing financial climate on a UK local charitable sector: voices from the front line. Issue 3 (16th April 2017) - Glennon, Russell; Hannibal, Claire; Meehan, Joanne
Abstract : Forced to compete with private and public sector providers, charities experience tensions as the quest for a more commercially-oriented position may conflict with their social imperative. Little attention has been given to understanding the experiences of local charities as service providers. This paper captures the reactions of those working on the charity front line.